Utilisation of postnatal care services among maternal in Maeen District - Sana'a City, Yemen - Abdulnasser A. Haza'a; Marzoq A. Odhah; Saddam A. Al-Ahdal; Fawz M. Abol-Gaith; Nada A. Ismail; Mohammed S. Al-Awar; Abdulfatah S. Al-Jaradi; Wedian S. Eidah; Manar M. Kaid (BMC, 2024)
Abstract Background One of the most effective ways to reduce maternal and neonatal mortality is to improve mother and newborn health via the provision of appropriate postnatal care services by qualified healthcare providers. However, there is limited information on the use of postnatal care services in Yemen. This study aimed to determine the utilisation of postnatal care services among mothers in Yemen. Methodology A descriptive cross-sectional study was conducted in the Maeen District of Sana'a City, Yemen from December 2022 to January 2023. Convenience sampling was employed to recruit 321 participants. Semi-structured questionnaires were applied as the study tool in the face-to-face survey. Result Less than half (45.2%) of the study participants utilised postnatal care services in this study. The mode of delivery, place of delivery, and receiving information about postnatal care during antenatal visits were significantly associated with postnatal care service utilisation. Conclusion Less than half of the study participants were informed about postnatal care services, contributing to their low utilisation. Thus, it is vital to strengthen the provision of information, education, and communication with regard to postnatal care services among pregnant mothers visiting antenatal clinics.